Questions about the Study of Cai Yuanpei and Peking University before and after the May Fourth Movement - Piyasirikul, Kampol (Journal of Sinology (วารสารจีนวิทยา), 2013)
During the past several decades, a large number of books and articles about Cai Yuanpei have been continuously published. This study involves a consideration of Cai’s political activities, political thoughts, educational ideas, his involvement with the May Fourth Movement, Cai’s Peking University reform and the relation between him and other contemporaries. Not only have the researchers on these topics studied quite deeply, but they have also achieved great success in obtaining new knowledge and publishing works for others to reference. Among this research, the study of Cai Yuanpei and Peking University before and after the May Fourth Movement is a “popular topic” relative to some others. After studying a great number of related research papers, the writer has found that there is a uniform recognition reached on this topic. However, the academic world is still divided on some issues. Thus, this article makes a brief summary of the content of related research papers, and then discusses the issues in dispute, including 1) Was Cai Yuanpei supported and incited by Dr.Sun Yat-sen to become the president of Peking University? 2) Did Cai Yuanpei support or oppose the May Fourth Movement? 3) Why did Cai Yuanpei resign? Finally, in view of the related research papers, the writer attempts to raise some new viewpoints and perspectives.